Cardiac Arrest in Pregnancy. Issue 4 (July 2015) - Killion, Molly
Abstract : Cardiac arrest during pregnancy is an event every obstetric and neonatal team hopes to avoid, however it remains a risk as our maternal population continues to have complicating comorbidities in pregnancy. Preplanning and multidisciplinary simulation may help to improve outcomes and team response.